Lutheran Ecclesiology - Jonathan Mumme (St Andrews Encyclopaedia of Theology, 2025)
Lutheran ecclesiology is an outgrowth of a reform movement within the Western church and shares scriptural underpinnings with this broader tradition. The Lutheran reformers’ convictions about the church and the basic contours of an ecclesiology found binding expression in the Lutheran confessions of the sixteenth century. Already in the sixteenth century, certain structural categories – often weighed in theologically productive pairings – began to shape and convey much of Lutheranism’s ecclesiology. The church’s visibility and hiddenness, faith and the means of grace, the nature and the marks of the church, and the relationship between congregation and ministry can all be diagnostically examined under the lens of internality and externality. Both the sixteenth-century confessions and subsequent works of Lutheran ecclesiology responded to the contexts in which they were forged, as the reformers and their historical heirs sought to think about and live as the church amid shifting social, philosophical, and political circumstances. Efforts over the last hundred years have therefore been shaped not just by the Confessions but also by theological developments from the Reformation to seventeenth-century orthodoxy, the Enlightenment, and the intellectual sea changes of the nineteenth century. Lutherans address some general theological concerns that relate to ecclesiology in a common manner. At the same time, Lutheran forms of ecclesial life have both reflected and framed more distinctly Lutheran theologies of the church along somewhat different trajectories, with Lutherans living under bishops, in state churches, in free churches, or often in some democratized amalgamation thereof. Modern Lutheran ecclesiological efforts have taken shape as regional or national groups of Lutherans have sought association, federation, and communion with one another, and as they have attempted ecumenical rapprochement with other Christians. Now informed by a polyphonic ecclesiological discourse in an increasingly secular age, Lutheran ecclesiologies seek to present the church as a creature of the gospel while articulating the place, role, and responsibility of Christians in and for this community.